2013
DOI: 10.1038/bjc.2013.484
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 receptor promotes cell invasion and metastasis in prostate cancer cells

Abstract: Background:Our previous study demonstrated that extracellular adenosine 5′-triphosphate (ATP) stimulated prostate cancer cell invasion via P2Y receptors. However, the purinergic receptor subtype(s) involved in this process remains unclear. Here we aimed to determine whether P2Y2, one subtype of P2Y receptors, was involved in the invasion and metastasis of prostate cancer cells, and elucidated the underlying mechanism.Methods:RNAi was introduced to silence the expression of P2Y2. In vitro invasion and migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 43 publications
6
111
0
1
Order By: Relevance
“…For instance, in two prostate cancer (PC) cell lines derived from PC-3cells, stimulationof one typeof P2Y receptor with ATP induced an increase in their migratory and invasive abilities, an action mediated by the activation of kinases ERK and p38 [86]. Eventually, P2Y2 was identified as one of the receptors responsible for the ATP-induced invasive response of the PC cells; the process involved the activation of the EMT program, since expression of the transcripts coding for Snail and IL-8 increased whereas those for E-cadherin and claudin decreased [87]. Further analysis of the molecular mechanism showed that P2Y2 receptor activation during EMTwas associated with EGFR activity.…”
Section: Purinergic Signaling Emt and Invasivenessmentioning
confidence: 99%
“…For instance, in two prostate cancer (PC) cell lines derived from PC-3cells, stimulationof one typeof P2Y receptor with ATP induced an increase in their migratory and invasive abilities, an action mediated by the activation of kinases ERK and p38 [86]. Eventually, P2Y2 was identified as one of the receptors responsible for the ATP-induced invasive response of the PC cells; the process involved the activation of the EMT program, since expression of the transcripts coding for Snail and IL-8 increased whereas those for E-cadherin and claudin decreased [87]. Further analysis of the molecular mechanism showed that P2Y2 receptor activation during EMTwas associated with EGFR activity.…”
Section: Purinergic Signaling Emt and Invasivenessmentioning
confidence: 99%
“…S1D). Among other requirements, the ability of tumor cells to migrate and invade adjacent structures depends on cellular energy production (21,22). To test whether altered PHD3 expression affected ATP production in tumor cells, we performed ATP assays under varying conditions.…”
Section: Phd3 Expression Affects Mitochondrial Atp Production Of Tumomentioning
confidence: 99%
“…P2Y2 receptor recognizes ATP and UTP ligands, and bind G-protein by phospholipase C (PLC) activation and mobilizing intracellular Ca 2+ (Li et al, 2011). This receptor subtype is involved in proliferation of certain tumors including lung (Schumacher et al, 2013), pancreas (Choi et al, 2013), prostate (Li et al, 2013) and breast (Li et al, 2011). In contrast, in colorectal cancer, this receptor blocks cell proliferation (Küntzli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%